Penggunaan Kadaver pada Praktikum Anatomi bagi Mahasiswa Fakultas Kedokteran - Zen, Suharno; Thamrin, Micko Martha; Fathurrohman, Ilham; Zakiyah, Miftahuz; Fajriyah, Nadya Syarifatul; Afgani, Maulana Al (Jurnal Sains, Teknologi dan Kesehatan, 2024)
The use of cadavers in practicums is an important and principle element in learning human anatomy. Cadavers as a tool in anatomy education help medical students to gain a concrete and three-dimensional understanding of the structure of the human body. By using cadavers, students can observe various body components, from the outer skin layer to internal organs such as blood vessels, nerves, muscles and other vital organs. Anatomy practicum involving the use of cadavers gives students a deeper understanding of spatial orientation and a three-dimensional understanding of human anatomy. This study aims to evaluate the use of cadavers in anatomy practicum for medical students. The method used is a literature study or narrative review which involves analysis of national and international journals related to the use of cadavers. The research results show that there are articles from national and international journals. The use of cadavers has proven to be the main method in studying anatomy that is able to provide medical students with an understanding of human anatomy in three dimensions. It is hoped that this review article can provide information regarding the use of cadavers in anatomy practicum for medical students. There is a need for other media in anatomy practicum or other anatomy learning media such as the use of Anatomage as a 3-dimensional (3D) visualization technology media.